Incidence and outcomes of acute high-risk chest pain diseases during pregnancy and puerperium - Wu, Shengyong; Xu, Xudong; He, Qian; Qin, Yingyi; Wang, Rui; Chen, Jun; Chen, Chenxin; Wu, Cheng; Liu, Suxuan (Frontiers in Cardiovascular Medicine, 2022)
Aim To investigate the incidence and outcomes of acute high-risk chest pain diseases, including acute myocardial infarction (AMI), aortic dissection (AD), and pulmonary embolism (PE) during pregnancy and puerperium. Methods The National Inpatient Sample was queried to identify pregnancy-related hospitalizations from January 1, 2008 to December 31, 2017. Temporal trends in the incidence and mortality of AMI, AD and PE were extracted. Results Among 41,174,101 hospitalizations, acute high-risk chest pain diseases were diagnosed in 40,285 (0.098%). The incidence increased from 79.92/100,000 in 2008 to 114.79/100,000 in 2017 (Ptrend < 0.0001). The most frequent was PE (86.5%), followed by AMI (9.6%) and AD (3.3%). The incidence of PE in pregnancy decreased after 2014 and was lower than AMI and AD, while its incidence in puerperium was higher than AMI and AD consistently (Ptrend < 0.0001). Subgroup analysis showed the incidence of these diseases was higher in black women, lowest-income households, and elderly parturients (Ptrend < 0.0001). The mortality decreased from 2.24% in 2008 to 2.21% in 2017 (Ptrend = 0.0240), exhibiting 200-fold higher than patients without these diseases. The following factors were significantly associated with these diseases: aged ≥ 45 years (OR, 4.25; 95%CI, 3.80–4.75), valvular disease (OR, 10.20; 95%CI, 9.73–10.70), and metastatic cancer (OR, 9.75; 95%CI, 7.78–12.22). The trend of elderly parturients increased from 14.94% in 2008 to 17.81% in 2017 (Ptrend < 0.0001), while no such up-trend was found in valvular disease and metastatic cancer. Conclusion The incidence of acute high-risk chest pain diseases, especially PE in puerperium, increased consistently. Although mortality has shown a downward trend, it is still at a high level. We should strengthen monitoring and management of acute high-risk pain diseases in pregnancy and puerperium, especially for black women, lowest-income households, and elderly parturients in the future.